KEBIJAKAN HUKUM PIDANA MEMPERTAHANKAN JENIS PIDANA MATI (STUDI KASUS PEMBUNUHAN BERENCANA DISERTAI MUTILASI KORBAN) - A.A. Sagung Mas Yudiantari Darmadi (University of Udayana, 2015)
The research was policy of criminal law maintains kind of death penalty (the case study ofplan murder while mutilates the victim), aims to describe and analyze the existence of thedeath penalty to the crime of plan murder. In addition, this study also aims to determinepolicies of criminal law related to death penalty for the crime of plan murder accompanied bymutilation as an aggravating. The method used in this research was conducted normativelyby reviewing the primary and secondary which was collected based on collecting methodof normative law and for the technique of collecting its legal entity were used documentertechnique i.e the technique to analyze and collect on various documents that already existsby applying some kind of approach, namely, the approach of legislation, and analyticalapproaches. The analysis of research was presented in form of descriptive-analytical,systematic, constructive and argumentative.The death penalty against the crime of murder is still maintained and in force today inIndonesia, as contained in the provisions of Article 340 of the Criminal Code. Capitalpunishment are recognized in the criminal offense of premeditated murder, but the deathpenalty was alternatifed with other criminal types namely life imprisonment and a maximumof 20 years. Death penalty imposed in the case of things that are burdensome. By it didnot published things that incriminate a crime in the Criminal Code, the judge only includethings that are burdensome and ease generally. This certainly can not be released that theprovisions of Article 197 paragraph (1) Criminal Code incriminating things was imperatively.Regarding the criminal law policy relating to the death penalty for the crime of murder waslisted in Article 581 of the Criminal Code. In this case, the RUU KUHP did not include theCriminal Code specifically mutilation as a criminal aggravating reasons, however whenseen from the provisions of Article 55 paragraph (1), the mutilation may be a motive andpurpose of committing a crime (letter b); how committed the crime (letter e); as well as theattitudes and actions of after committing a crime (letter f).